A Call for Rethinking Schooling and Leadership in the Time of COVID-19 - Rincones, Rodolfo; Peña, Isela; Canaba, Karina Chantal (Frontiers in Education, 2021)
COVID-19 forced a sudden closure of schools, prompting a hasty and unplanned reaction of educators to deliver educational content. Inspired by Ivan Illich’s book Deschooling Society, we reflect on ways to visualize the delivery of educational content by utilizing technology and forging intentional partnerships with parents and communities to assist in the delivery of educational content. This “forced” deschooling has offered educators an opportunity to rethink the true purpose of education, and redesign flexible, creative and innovative instructional strategies for delivering educational materials and knowledge, as well as rethinking the role of and preparation of educational leaders. While we do not offer quick solutions, our intent is to revisit Illich’s Deschooling Society as a means to examine and question our school system introspectively and collectively.